Analisis Peraturan Menteri Perhubungan N0. 27 Tahun 2018 Tentang Alat Penerangan Jalan terkait Lampu Penerangan Jalan (Lampu Pocong) Dikota Medan di Tinjau dari Persfektif Fiqh Siyasah - Ramadhan, Solihin; Fatimah, Fatimah (UNES Law Review, 2023)
Street lighting is one of the regional government services that is used for the benefit of the general public in daily life. Minister of Transportation Regulation No. 27 of 2018 concerning Public Street Lighting Equipment is to optimize road equipment facilities in the form of street lighting devices. In order to realize safety, security, order and smooth traffic as well as convenience for road users in traffic. Providing street lighting facilities is a form of successful development in an area. However, the reality found in the field is that there are still street lights in the city of Medan that are not functioning or are not on. Malfunctioning of street lights can cause accidents, theft, and so on for road users. Therefore, the physical form and function of street lights must be in accordance with the regulations or procedures, and also the form of operation of street lights must be in accordance with the needs of the community in general and avoid waste and wasteful use of resources and budgets as explained in Minister of Transportation Regulation Number 27 of 2018 concerning Street Lighting Equipment that the government does not implement the points in this regulation properly, so the construction of public facilities for street lighting. From the perspective of Fiqh Siyasah, and Minister of Transportation Regulation no. 27 concerning Street Lighting Equipment, there are still many things that are not in accordance with the provisions of Siyasah Fiqh.